The sequence a 0 , a 1 , a 2 , … satisfies a m + n + a m − n = 2 1 ( a 2 m + a 2 n )
for all non-negative integers with m ≥ n . If a 1 = 1 , determine the value of a 1 9 9 5
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I did the almost same thing !....but instead of induction i solved the recursion directly
Log in to reply
How did u solve the recursion directly? Can you post ur soln. Here?
Log in to reply
I will show here how can you solve the recursion
a
m
+
1
=
2
a
m
−
a
m
−
1
+
2
(
∗
)
subject to
a
0
=
0
,
a
1
=
1
,
and
a
2
=
4
.
This recurrence and the initial values can be obtained like it was done by
@Daniel Liu
in his solution here.
Making
m
=
n
−
1
and
m
=
n
−
2
into the recurrence relation, where
n
≥
3
,
we obtain
a
n
=
2
a
n
−
1
−
a
n
−
2
+
2
and
a
n
−
1
=
2
a
n
−
2
−
a
n
−
3
+
2
,
respectively. By subtracting the second equation from the first and solving for
a
n
,
we get that
a
n
=
3
a
n
−
1
−
3
a
n
−
2
+
a
n
−
3
.
The characteristic polynomial of this linear recurrence is
(
r
−
1
)
3
.
Using the results explained in the wiki
Linear Recurrence Relations with Repeated Roots,
we obtain that
a
n
=
c
1
+
c
2
n
+
c
3
n
2
.
That is,
a
n
will be the linear combination of the sequences
1
,
n
,
and
n
2
.
Using the initial conditions we get the equations
c
1
=
0
,
c
1
+
c
2
+
c
3
=
1
,
and
c
1
+
2
c
2
+
4
c
3
=
4
.
and solving this system of equations we get that
c
1
=
0
,
c
2
=
0
,
and
c
3
=
1
.
Therefore,
a
n
=
n
2
.
The last step would be to show that
a
n
=
n
2
satisfies
(
∗
)
.
So this is the only solution of
(
∗
)
subject to the given initial conditions.
series formed is 0, 1, 4, 9, 16, 25.... by putting different values of n and m
Problem Loading...
Note Loading...
Set Loading...
Let P ( m , n ) be the statement a m + n + a m − n = 2 1 ( a 2 m + a 2 n ) .
First off, P ( 0 , 0 ) gives a 0 + a 0 = 2 1 ( a 0 + a 0 ) ⟹ a 0 = 0
Then, P ( 1 , 0 ) gives a 1 + a 1 = 2 1 ( a 2 + a 0 ) ⟹ a 2 = 4
Then, P ( m , 0 ) gives a m + a m = 2 1 ( a 2 m + a 0 ) ⟹ a 2 m = 4 a m
Now, P ( m , 1 ) gives a m + 1 + a m − 1 = 2 1 ( a 2 m + a 2 ) ⟹ a m + 1 + a m − 1 = 2 a m + 2
So we have the recursive equation a m + 1 = 2 a m − a m − 1 + 2
Now we proceed by induction to prove that all a m = m 2 .
Base cases: a 0 = 0 and a 1 = 1 .
Now assume a k = k 2 and a k − 1 = ( k − 1 ) 2 . We see that a k + 1 = 2 k 2 − ( k − 1 ) 2 + 2 = k 2 + 2 k + 1 = ( k + 1 ) 2
Thus, all a m = m 2 and our answer is a 1 9 9 5 = 1 9 9 5 2 = 3 9 8 0 0 2 5 .